Constancy, uniformity and symmetry of living systems: the computational functions of morphological invariance - Elitzur, Avshalom C (BioSystems, 1997)
Living systems, whether organs or entire organisms, display various forms of morphological invariance. Why? These phenomena are studied here from the Proto-Cognitive perspective, according to which evolution proceeds by processing information about the environment. The evolution of constancy, uniformity and symmetry is studied in detail. The study later focuses on the invariances of the plant's leaves and it is proposed that these invariances play a crucial role in the plant's development of individual form. Experiments are proposed to test these hypotheses. Morphological invariance is further examined in the light of thermodynamics and information theory. New thermodynamic restrictions are imposed on the processes of measurement and information recording. Uniformity and symmetry are shown to meet these restrictions.